The role of tradition in moral decision- making and moral consensus - Koopman, NN (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
This article investigates the role of tradition in the processes of moral decision-making and moral consensus in a pluralistic society. This question is addressed by focusing on the work of two scholars with opposing views on this theme. Harry Kuitert represents the so- called liberal approach which argues in favour of a tradition-independent understanding of morality, moral decision-making and moral consensus. Stanley Hauerwas is a representative of the so-called postliberal approach to morality. According to him morality, moral decision-making and the quest for moral consensus take place in dependence on notions like virtues, narratives and community. After the outline of these positions suggestions are made with regard to lessons that can be learned from both approaches for the ongoing moral discourse in pluralistic societies like South Africa.